Competition and Environment : Conflict or Confluence ? Some Reflections on Sustainability Agreements Under Article 101(3) of the TFEU - De Leonardis, Francesco Carretero (Revista Amagis Jurídica, 2025)
1 The intersections between competition law and environmental law. 2 The competition principle in the Italian Environmental Code. 2.1 The competition principle ends the municipal monopoly in waste collection. 2.2 Competition principle and EPR schemes. 3. “Improving the production”: the environmental way. 4. Conclusions on sustainability agreements. References.